Funcionamiento familiar y riesgo de embarazo en adolescentes, Guadalupe - La Libertad, 2021 - Seminario Guanilo, Juliana Caroline (2022)
The present investigation is quantitative, descriptive, correlational, it was carried out in the year 2021, with the objective of determining the relationship that exists between family functioning and the risk of pregnancy in adolescents of 4th and 5th year of secondary school of the Institution Educative Eduvigis Noriega de Lafora N° 35 – Guadalupe. The sample consisted of 90 adolescents, to whom two instruments were applied, the first measures family functioning and the second measures the risk of adolescent pregnancy. The results show that 50 percent of adolescents have a balanced level of family functioning; 34.4 percent, medium family functioning and 15.6 percent, extreme family functioning; 54.4 percent of adolescents have a low risk of pregnancy; 23.3 percent high risk of pregnancy and 22.2 percent without risk of pregnancy; a Spearman Brown correlation of 0.560 is evidenced, with a significance lower than the value 0.05 (0.000 < 0.05), for which it is concluded that there is a significant relationship between family functioning and the risk of adolescent pregnancy